Conclusion: Ten Principles for the Study of Proportional Systems in the History of Architecture. Issue 1 (20th June 2014) - Cohen, Matthew A.
Abstract : The study of proportional systems today lacks a common framework for discussion. In this conclusion to the special collection of essays on this topic published in Architectural Histories, Matthew A. Cohen provides ten principles as a basis for future discussion on this complex topic.